2018
DOI: 10.15171/ijhpm.2018.68
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Enrolment in the National Health Insurance Scheme Among Women of Reproductive Age in Nigeria

Abstract: Background: Despite the implementation of the National Health Insurance Scheme (NHIS) since 2005 in Nigeria, the level of health insurance coverage remains low. The study aims to examine the predictors of enrolment in the NHIS among women of reproductive age in Nigeria. Methods: Secondary data from the 2013 Nigeria Demographic and Health Survey (NDHS) were utilized to examine factors influencing enrolment in the NHIS among women of reproductive age (n=38 948) in Nigeria. Demographic and socio-economic charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
43
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 47 publications
22
43
6
Order By: Relevance
“…Being a worker was a significant predictor of health insurance coverage among women in this study. This finding is consistent with similar studies done in Africa [15,26]. The possible reason could be employed women are economically empowered to pay premium contributions than the unemployed once.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Being a worker was a significant predictor of health insurance coverage among women in this study. This finding is consistent with similar studies done in Africa [15,26]. The possible reason could be employed women are economically empowered to pay premium contributions than the unemployed once.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous studies [13,[15][16][17], the current study showed that the likelihood of being covered by health insurance was highest among educated women as compared with women with no education. The possible explanation could be educated women have more knowledge about the advantages of health insurance and make informed choices, engage themselves in different knowledge enhancement activities like reading materials, give more concern for their health and insure themselves against the unexpected out-of-pocket payments.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations